Effect of pretreatment on the formation of 5-chloromethyl furfural derived from sugarcane bagasse. Issue 7 (12th January 2016) - Howard, Joshua; Rackemann, Darryn W.; Zhang, Zhanying; Moghaddam, Lalehvash; Bartley, John P.; Doherty, William O. S.
Abstract : The highest CMF yield (81.9%) was achieved with acidic ionic liquid pretreated bagasse, which had a glucan content of 81.6%. Abstract : Chloromethylfurfural (CMF), a valuable intermediate for the production of chemicals and fuels, can be derived in high yields from the cellulose component of biomass. This study examined the effect of sugarcane bagasse components and biomass architecture on CMF/bio-oil yield using a HCl/dichloroethane biphasic system. The type of pretreatment affected bio-oil yield, as the CMF yield increased with increasing glucan content. CMF yield reached 81.9% with bagasse pretreated by acidified aqueous ionic liquid, which had a glucan content of 81.6%. The lignin content of the biomass was found to significantly reduce CMF yield, which was only 62.3% with an acid-catalysed steam exploded sample having a lignin content of 29.6%. The change of CMF yield may be associated with fibre surface changes as a result of pretreatment. The hemicellulose content also impacted negatively on CMF yield. Storage of the bio-oil in chlorinated solvents prevented CMF degradation.